2016
DOI: 10.1016/j.jtusci.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Predictive modelling of the LD50 activities of coumarin derivatives using neural statistical approaches: Electronic descriptor-based DFT

Abstract: A study of structure-activity relationship (QSAR) was performed on a set of 30 coumarin-based molecules. This study was performed using multiple linear regressions (MLRs) and an artificial neural network (ANN). The predicted values of the antioxidant activities of coumarins were in good agreement with the experimental results. Several statistical criteria, such as the mean square error (MSE) and the correlation coefficient (R), were studied to evaluate the developed models. The best results were obtained with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…It is observed that the correlation coefficient r is very high and that the mean squared error value (MSE) is low, which makes it possible to indicate that the model is more reliable. A P value much smaller than 0.05 indicates that the regression equations are statistically significant, and we can conclude, with confidence, that the model provides a significant amount of information [12].…”
Section: Multiple Linear Regression (Mlr)mentioning
confidence: 56%
“…It is observed that the correlation coefficient r is very high and that the mean squared error value (MSE) is low, which makes it possible to indicate that the model is more reliable. A P value much smaller than 0.05 indicates that the regression equations are statistically significant, and we can conclude, with confidence, that the model provides a significant amount of information [12].…”
Section: Multiple Linear Regression (Mlr)mentioning
confidence: 56%
“…Three components constitute a neural network: the processing elements or nodes, the topology of the connections between the nodes, and the learning rule by which new information is encoded in the network. Although there many different ANN models, the most frequently used type of ANN in QSAR is the three-layered feed forward network [17]. In this type of network, the neurons are arranged in layers as an input layer, one hidden layer and an output layer.…”
Section: Discussionmentioning
confidence: 99%
“…Three components constitute a neural network: the processing elements or nodes, the topology of the connections among the nodes, and the learning rule by which new information is encoded in the network. Although there many different ANN models, the most frequently used type of ANN in QSAR is the three-layered feed-forward network [31]. In this type of network, the neurons are arranged in layers as an input layer, a hidden layer and an output layer.…”
Section: Discussionmentioning
confidence: 99%